Increased Perceived Confidence in Professional Role Skills among Undergraduate Dietetic Students Following Simulation-Based Learning Experiences - Makenzie Barr-Porter; Elizabeth Combs; Lauren Batey; Dawn Brewer; Aaron Schwartz; Tammy Stephenson (MDPI AG, 2024)
Simulation-based learning experiences (SBLEs) are effective for teaching healthcare students clinical and communication skills. The current study assessed self-perceived clinical and communication confidence among dietetics students completing a series of four SBLEs (3 group, 1 individual) across nine months. Dietetics students were recruited in February 2023 prior to their first SBLE. Simultaneously through the academic year, students completed clinical and communication courses. Students were invited to complete an online, anonymous self-reported survey regarding confidence with nutrition care and communication prior to their first SBLE (Time 1), prior to their third SBLE (Time 2), and following their final SBLE (Time 3). The survey measured healthcare work experience and self-perceived confidence. Student confidence increased among 30 of the 38 indicators (p < 0.05). At Time 2 (following two group SBLEs), those with healthcare experience had higher confidence among 12 of the 39 items (p < 0.05). At Time 3 (following four simulation experiences) those with healthcare experience had higher confidence among just four of the 39 total items (p < 0.05). Cohort increases in confidence suggest that SBLEs, along with dietetics coursework, were critical in increasing confidence and students' perceived ability to carry-out entry-level tasks of a dietitian. While student confidence increased across the cohort, SBLEs were particularly beneficial in leveling confidence between those with prior clinical experience and those without.